2016
DOI: 10.1007/s12024-016-9787-8
|View full text |Cite
|
Sign up to set email alerts
|

Can postmortem computed tomography detect antemortem hypoxic–ischemic encephalopathy?

Abstract: The purpose of this study was to evaluate the usefulness of brain postmortem computed tomography (PMCT) findings for the detection of global hypoxia or hypoperfusion leading to hypoxic-ischemic encephalopathy (HIE) prior to death. Cadavers of individuals who died from non-traumatic causes were subjected to PMCT and pathological autopsy. Cases with an episode of cardiopulmonary arrest, hypoxia, or hypoperfusion that required intensive respiratory management at least 24 h before death and exhibited findings of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…The antemortem CT findings of loss of gray and white matter differentiation and symmetrical, low-density cerebral edema have typically been reported for hypoxic–ischemic encephalopathy on antemortem CT [14] , consistent with the present case. The postmortem CT findings of sulcal effacement of the cerebral hemisphere and the loss of contrast at the basal ganglia are characteristic findings of hypoxic–ischemic encephalopathy on postmortem CT [7] , [8] , [9] , [10] , [11] , which were also consistent with the present case. Furthermore, in the present case, we observed delayed enhancement of deep gray matter, such as the caudate nucleus and putamina, on postmortem CT. To the best of our knowledge, this is the first report on these postmortem CT findings.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The antemortem CT findings of loss of gray and white matter differentiation and symmetrical, low-density cerebral edema have typically been reported for hypoxic–ischemic encephalopathy on antemortem CT [14] , consistent with the present case. The postmortem CT findings of sulcal effacement of the cerebral hemisphere and the loss of contrast at the basal ganglia are characteristic findings of hypoxic–ischemic encephalopathy on postmortem CT [7] , [8] , [9] , [10] , [11] , which were also consistent with the present case. Furthermore, in the present case, we observed delayed enhancement of deep gray matter, such as the caudate nucleus and putamina, on postmortem CT. To the best of our knowledge, this is the first report on these postmortem CT findings.…”
Section: Discussionsupporting
confidence: 89%
“…According to previous studies examining brain postmortem CT, the loss of gray and white matter differentiation, diffuse brain swelling, and pseudo-subarachnoid hemorrhages were often observed in nonpathological brains and hypoxic–ischemic encephalopathy [7] , [8] , [9] , [10] , [11] . Another study examining voxel-based analyses reported a rapid decrease in cortical gray matter density combined with a delayed increase in white matter density [12] .…”
Section: Introductionmentioning
confidence: 95%
“…In the very early postmortem period, loss of gray–white matter differentiation because of cellular edema is rarely accompanied by severe brain swelling [ 32 ]. Changes in basal ganglia density may help distinguish these from postmortem changes [ 66 ]. In addition, a gross neck mass that narrows the airway can be determined by postmortem CT [ 67 ].…”
Section: Diagnosable or Non-diagnosable Pathology On Non-contrast-enh...mentioning
confidence: 99%
“…The results showed that there was a tendency to increase brain weight in patients with TA, with severe cerebral vascular congestion, perivascular hemorrhage and occasional β‐APP deposition, which was consistent with early axonal destruction (Al‐Sarraj S, et al, 2017). Some studies have shown that if a patient has hypoxic‐ischemic encephalopathy (HIE) before death, the disappearance of cerebral hemispheric sulcus and the loss of contrast at the basal ganglia level can be found by computer tomography (PMCT) after brain death (Shirota G, et al, 2016). From the above results, it can be found that different parts of the brain have different morphological and pathological changes after cerebral ischemia.…”
Section: Morphology and Pathology Of Cerebral Ischemiamentioning
confidence: 99%